Nagygomba-felmérés Gyűrűfű környékén - Pál-Fám, Ferenc; Morschhauser, Tamás; Rudolf, Kinga (Natura Somogyiensis, 2009)
During the I. and II. Hungarian Biodiversity Day a total number of 180 macrofungi taxa were documented in a 1 km2 sample plot near Gyűrűfű village. The general functional spectra showed the lignicolous saprotrophic group the biggest (67 species, 37%), but the proportion of mycorrhizal (44 species, 24%) and soil inhabiting saprotrophic (42 species, 23%) functions were also significant. The 19 species and 11% proportion of the necrotrophic parasites indicates the lack of forestry management in the territory, as well as its good species retentiveness. One single protected species were documented: Creolophus cirratus. According to this preliminary survey, a detailed examination of the fungal communities is important in the close future.